MATHEMATICAL MODEL OF POWER CONSUMPTION FOR SOME OIL PIPE-LINE SECTIONS WITH POOR OPERATIONAL STABILITY - J. N. Kolesnik; N. V. Tokochakova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Mathematical model of power consumption for technologically completed and non-completed oil pipe-line sections with poor operational stability has been developed on the basis of daily indices concerning oil transportation regimes. The model permits to take into account tendencies in power consumption under various time prediction cycles and ranges of oil freight turnover, changes in the bulk and characteristics of the transported oil, configuration and design parameters of oil pipe-line.